A permanência dos princípios judaico-cristãos do perdão e da pena no atual direito penal brasileiro - Rocha, João Franco Muniz da (2007)
This Works studies, departing from Deuteronomy, Law of Aliance principles permanence, arisen from divine source and commited to Chosen People obedience, in Brazilian Law. Considered as natural Law, since it is, already, in each man heart, it has directed, has led Jewish people destiny, based on a social equilibrium attained through, with pardon concession, in case of Law violation. Decalog, especially, in regard to the commandments related to rapports among men, assumes a Project of Life role that survived through History, to all the occurred changes. Among the last ones, secularization and radical transformations in economics and the aims pursued by State. Those Jewish-Christian religion principles permanence that rule penalty and pardon, in modern Penal Law from State source, meant for disciplining behaviours in so diversified society, is permanence, mark of the sacred